Embolization of an angiomyolipoma in a crossed fused renal ectopia - Waseem Tayeb; Raghad Aldibane; Almamoon Justaniah; Hattan Badr (Urology Case Reports, 2020)
‏: Crossed fused ectopic kidney represents a rare congenital malformation, and development of an angiomyolipoma (AML) in a crossed fused ectopia is even rarer. There is no clear association between both entities. However, approximately half of crossed fused renal ectopic patients may develop infections, obstruction and/or nephrolithiasis. Nevertheless, they are very rarely associated with carcinoma. To our knowledge, this is the first case of AML in crossed fused renal ectopia. In this report, we present a patient with a left renal angiomyolipoma in a crossed fused renal ectopia managed by embolization. In addition, a literature review for relevant cases will be provided.